Datasets for multi-scale diffraction analysis (synchrotron XRD and EBSD) of twinning-detwinning during tensile-compressive deformation of AZ31B magnesium alloy samples - Zhang, H; Jérusalem, A; Salvati, E; Papadaki, C; Fong, K; Song, X; Korsunsky, A (Elsevier, 2019)
Diffraction data were collected using synchrotron X-ray scattering (sXRD) and electron back-scattered diffraction (EBSD) during in situ tensile-compressive deformation of Mg alloy AZ31B dogbone samples. The onset and evolution of twinning and detwinning were monitored based on intensity changes in sXRD 2D scattering patterns (which also provided average elastic strain values through the calculation of orientation-specific lattice spacing changes), and EBSD, that revealed the micro-scale grain morphology changes. The observations were interpreted and analysed with the help of crystal plasticity finite element modelling (CP-FEM), as reported in the published article (https://doi.org/10.1016/j.ijplas.2019.02.018).